A readily usable two‐photon fluorescence lifetime microendoscope. Issue 5 (2nd January 2019) - Hage, Charles‐Henri; Leclerc, Pierre; Fabert, Marc; Bardet, Sylvia M.; Brevier, Julien; Ducourthial, Guillaume; Mansuryan, Tigran; Leray, Aymeric; Kudlinski, Alexandre; Louradour, Frédéric
Abstract : A two‐photon fluorescence lifetime (2P‐FLIM) microendoscope, capable of energetic metabolism imaging through the intracellular nicotinamide adenine dinucleotide (NADH) autofluorescence, at sub‐cellular resolution, is demonstrated. It exhibits readily usable characteristics such as convenient endoscope probe diameter (≈2 mm), fiber length (>5 m) and data accumulation rate (16 frames per second (fps)), leading to a FLIM refreshing rate of ≈0.1 to 1 fps depending on the sample. The spiral scanning image formation does not influence the instrument response function (IRF) characteristics of the system. Near table‐top microscope performances are achieved through a comprehensive system including a home‐designed spectro‐temporal pulse shaper and a custom air‐silica double‐clad photonic crystal fiber, which enables to reach up to 40 mW of ≈100 fs pulses @ 760 nm with a 80 MHz repetition rate. A GRadient INdex (GRIN) lens provides a lateral resolution of 0.67 μm at the focus of the fiber probe. Intracellular NADH fluorescence lifetime data are finally acquired on cultured cells at 16 fps. Abstract : Label‐free optical biopsy in vivo in real‐time represents a major alternative to time‐consuming standard histology of surgical biopsies. Thus, an endomicroscope capable of imaging unstained living cells in situ has been a long lasting research subject. This paper brings the first demonstration of two‐photon excited auto‐fluorescence lifetime imaging of cell energetic metabolism in a clinically usable configuration and makes a decisive step towards advanced endoscopy.